The Soviet Government’s Attitude Toward Waqf Properties - Qalandarov Hamza (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article discusses the traditional Waqf system in Central Asia, the Soviet government’s attitude towards Waqf properties, the contradictions between the authoritarian regime, local population, and religious scholars, as well as the consequences of these conflicts. Additionally, it analyzes the Soviet government’s land and water policies and the laws and decrees it issued in this regard.